Performance Analysis of Sharia Banking Using The Educatian Prism Method: Case Study Pt. Bank Muammalat Sumatera Utara - Atika Atika; Saparuddin Siregar; Sugianto Sugianto (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Using the performance prism method, this study aims to determine and analyze the performance of Islamic banking at PT. Bank Muammalat. The Performance Prism method is a performance measurement model that depicts organizational performance as a three-dimensional shape (prism) with five sides. This model considers satisfaction, stakeholder contribution, process, and company capability in addition to strategy. This is a quantitative study with a descriptive approach. The results showed that PT. Bank Muamalat performance is already good, as evidenced by the overall Total Index value of 6.2331. Whereas a score of 6-7 indicated that the resulting performance was good according to the provisions of the OMAX Achievement Target.